The impact of information sources on COVID-19 vaccination intentions among pre-service life sciences teachers in South Africa: A cross-sectional study - Lindelani MNGUNI; Moleboheng RAMULUMO (Journal of Health and Social Sciences)
Introduction: The COVID-19 pandemic underscored the importance of health literacy, where pre- service Life Sciences teachers can promote safe behavioral practices such as vaccination. However, the health information sources influencing their behavioral intentions toward vaccination are poorly understood. This study examines how different sources impact vaccination attitudes and behaviors Methods: A cross-sectional study was conducted involving pre-service Life Sciences teachers (n = 87) from a South African university. Data were collected using a closed-ended questionnaire to explore the types of information sources they use and how these sources influence their attitudes, subjective norms, and perceived behavioral control related to COVID-19 vaccination. Results: Participants utilized a diverse array of information sources, including government communiques, traditional media, social media, research publications, and personal interactions. Although the susceptibility to misinformation from unreliable sources such as social media was identified, participants' scientific training served as a buffer against such misinformation. Notably, the type of information source did not significantly predict subjective norms and perceived behavioral control. However, information sources significantly influenced attitudes and normative beliefs toward vaccination. Discussion: The study underscores the complex relationship between information sources, cognitive processes, and behavioral intentions in the context of health literacy among pre-service Life Sciences teachers. The findings suggest that while their scientific background provides a defense against misinformation, targeted strategies are essential to ensure the reliability and validity of information. Further research is warranted to understand additional factors influencing this demographic's vaccination intentions and to inform more effective health literacy initiatives. This research bears significant implications for public health communication strategies, particularly in a pandemic.